2023
DOI: 10.7554/elife.81522
|View full text |Cite
|
Sign up to set email alerts
|

Participation in the nationwide cervical cancer screening programme in Denmark during the COVID-19 pandemic: An observational study

Abstract: Background: In contrast to most of the world, the cervical cancer screening programme continued in Denmark throughout the COVID-19 pandemic. We examined the cervical cancer screening participation during the pandemic in Denmark. Methods: We included all women aged 23-64 years old invited to participate in cervical cancer screening from 2015-2021 as registered in the Cervical Cancer Screening Database combined with population-wide registries. Using a generalised linear model, we estimated prevalence ratios (PR)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
1
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 18 publications
2
5
1
4
Order By: Relevance
“…This indicates that the restrictions imposed in Denmark may have affected some groups of women disproportionally. A study from Spain Bosch et al, 2022 found that the participation in mammography screening decreased with age and with lower socio-economic level post-COVID-19; this has also been reported for the two other screening programmes in Denmark ( Olesen et al, 2023a ; Olesen et al, 2023b ; this study). The evidence is scarce on participation according to ethnicity throughout the pandemic; however, the lower participation during the pandemic has also been demonstrated for bowel and cervical cancer screening in Denmark ( Olesen et al, 2023a ; Olesen et al, 2023b ; this study).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This indicates that the restrictions imposed in Denmark may have affected some groups of women disproportionally. A study from Spain Bosch et al, 2022 found that the participation in mammography screening decreased with age and with lower socio-economic level post-COVID-19; this has also been reported for the two other screening programmes in Denmark ( Olesen et al, 2023a ; Olesen et al, 2023b ; this study). The evidence is scarce on participation according to ethnicity throughout the pandemic; however, the lower participation during the pandemic has also been demonstrated for bowel and cervical cancer screening in Denmark ( Olesen et al, 2023a ; Olesen et al, 2023b ; this study).…”
Section: Discussionsupporting
confidence: 82%
“…A study from Spain Bosch et al, 2022 found that the participation in mammography screening decreased with age and with lower socio-economic level post-COVID-19; this has also been reported for the two other screening programmes in Denmark ( Olesen et al, 2023a ; Olesen et al, 2023b ; this study). The evidence is scarce on participation according to ethnicity throughout the pandemic; however, the lower participation during the pandemic has also been demonstrated for bowel and cervical cancer screening in Denmark ( Olesen et al, 2023a ; Olesen et al, 2023b ; this study). Immigrants may find it more difficult to navigate the healthcare system in Denmark, and possibly this has been exacerbated by the pandemic where the majority of the communication at press conferences and news media were conveyed in Danish, a language that may not be fully comprehensive to all immigrants.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…We found an overall 5–10% increased participation in colorectal cancer screening from first re-opening and onwards. We did not find an increased participation in the other cancer screening programmes (breast and cervical cancer) in Denmark ( Olesen et al, 2023 ; Olesen et al, 2022 ) most likely because those programmes require contact with the healthcare system. A home-based self-collected screening sample thus appear to work well during a pandemic, which could be used in other programmes, for example, cervical cancer screening.…”
Section: Discussioncontrasting
confidence: 56%
“…Through the ICD-10 diagnosis code searches and the subsequent hospital file reviews, we identified 114 patients through the DNPR search and 14 patients through the tertiary hospital registries, resulting in a national cCPHD cohort of 128 patients (Table S1 ( 23 )). Of these, 116 were born in Denmark and diagnosed before age 18 years, representing the national incidence cohort of cCPHD diagnosed <18 years ( Fig.…”
Section: Resultsmentioning
confidence: 99%